THE EFFECTIVENESS OF USING INTERACTIVE METHODS IN GEOGRAPHY LESSONS (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This article highlights the effectiveness of using interactive methods in the educational process of geography lessons. During the study, the impact of interactive methods on students’ level of knowledge acquisition, interest in the lesson, and activity was analyzed. Based on the results of pedagogical experimentation, observation, surveys, and assessment tasks, it was determined that interactive methods yield higher results compared to traditional teaching methods. The research findings demonstrate the importance of using modern pedagogical technologies in teaching geography.